PATHOLOGICAL SIGNS THAT OCCUR IN COGNITIVE PROCESSES AND THEIR ANALYSIS - Tojiddinova Laylokhan Shokirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides information about the patalogy of cognitive processes. According to him, the causes of the origin of several psychological diseases. The fact that they can be congenital or acquired. A number of guidelines are given to alleviate and prevent their causes and consequences. Violation of the senses is known more than everyone when the activity of the periphyric sections of the analyzers is lost. At this time, it is necessary that we all have enough information about who to contact and what measures should be taken.